KOMUNIKASI VERBAL FOTOGRAFER DAN MODEL DALAM PROSES PEMOTRETAN - Wiki Angga Wiksana (Jurnal Nomosleca, 2018)
AbstractPhotographers can not be separated from social interaction or commonly called human relations, both in communicating with photo models, assistants, teams, and the surrounding environment. The most common area of ​​photography among human interactions is model photography, because in this field the object of the photograph ishuman. In this study, there will be at least two people who interact, ie between the photographer and his model. This study aims to reveal the meaning of verbal interaction of photographers and models in the process of making photographs. The research method used is the interpretive approach study is a method that aims to interpret the case or subject studied. In this case, the data collection technique is done by in-depth interview, observation, and documentation study. The test data validity is done trianggulasi techniques, discussions with colleagues, and member check. The result of this interpretive approach is the verbal interaction of photographers and photo models in the process of making the photographs vary, depending on the photographer and the model determining the role. The verbal interaction of photographers and models will be harmonious, harmonious, and balanced in accordance with ethical and moral values, if both parties respect each other's profession and primarily uphold the ethical elements in the profession.Keywords: Verbal Communication, Photographers, Models, ShootingDOI : https://doi.org/10.26905/nomosleca.v4i1.1988